Spatial distribution characteristics and influencing factors of intangible cultural heritage in Shanxi Province, China - Zhao, Lijin; Liu, Min; Zhang, Shiqing; Yan, Xiuzhen (Frontiers in Earth Science, 2026)
Shanxi Province carries a profound historical and cultural accumulation and diversified regional and cultural characteristics. Comprehensive research on the spatial Characteristics of intangible cultural heritage in Shanxi Province and its influencing factors is of great academic significance for the protection and inheritance of China’s traditional cultural. This research focuses on 1,178 items of intangible cultural heritage in Shanxi Province, utilizing GIS spatial analysis techniques such as nearest neighbor index, kernel density estimation, and geographical detecto to investigate the spatial distribution patterns, and influencing factors of 1,178 intangible cultural heritage items documented across 11 municipal-level administrative units within Shanxi Province. Research shows: Shanxi’s intangible cultural heritage is generally distributed in a significant cluster state, and its spatial distribution characteristics are highly dense in central Shanxi, significantly clustered in southern Shanxi, and relatively dispersed in northern Shanxi, forming an overall structural feature of “four-core and two-belt”. In terms of influencing factors, cultural environmental factors have the most significant impact on the distribution of intangible cultural heritage, followed by socioeconomic factors. Natural geographic factors have a relatively minor direct impact on the distribution of intangible cultural heritage, but they indirectly influence it through interactions with other factors, which indicates that the distribution of intangible cultural heritage is the result of the joint action of natural support, social and economic evolution and cultural ecological construction. Finally, research proposes: the sustainable development of intangible cultural heritage in Shanxi Province should be realized by strengthening the construction of cultural institutions, improving the standard of education and promoting the integration of culture and tourism.